Electrical and microstructural changes of β-PVDF under uniaxial stress studied by scanning force microscopy - Nunes, J. Serrado (2006)
Chain reorientation may be induced in polyvinylidene fluoride (PVDF) in its β-phase by applying a deformation perpendicular to the pre-oriented polymeric chains. This reorientation begins right after the yielding point and seems to be completed when the stress-strain curve stabilizes. As the deformation process plays an important role in the processing and optimisation properties of the material for practical applications, different deformation stress was applied to the PVDF lamellas and their topographic change and piezoelectric response were studied by means of scanning force microscopy in a piezo-response mode. The experimental results confirm the previously observed chain reorientation that occurs right after the yielding point and that is completed when the yielding region is passed. This reorientation is accompanied by a stretching of the granular structures observed in the topographical images and variations in the domain response. The observed results help to explain the variations in the macroscopic response of the material.